Quantum mechanics - Schwabl, Franz, 1938-2009 (Springer-Verlag, 1992)
A student's first course in quantum mechanics provides the foundation essential for much of his or her future work in physics, be it in atomic, elementary particle or solid state physics. This introductory textbook contains not only the foundations and many applications of quantum mechanics, but also new aspects and their experimental verification. In the introductory chapters, starting from the historical evolution of the subject, the fundamental postulates are developed inductively by means of an interference experiment. Thereafter the structure is purely deductive, covering all of non-relativistic quantum mechanics, plus the quantization of the radiation field in the context of optical transitions. As well as the quantum mechanical "essentials" - for instance, detailed treatments of scattering theory, time dependent phenomena, and the density matrix - such topics as the theory of quantum mechanical measurement and the Bell inequality are discussed. A separate chapter is devoted to supersymmetric quantum mechanics, an area which to date has been accessible only in research literature.